Shadow Economic Activities: Assessment and Minimization Problems - Baizakov, Daniyar; Kari, Anuarbek (International Journal of Economics and Financial Issues, 2016)
In the modern context, when official national economies face permanent problems and are not always able to ensure desired living standards for population, the fight against shadow economic activities become crucial for all countries. It cannot be won without the development of a nuanced methodology for its assessment. We proposed a new methodology based on the study of different research approaches and methods regarding the assessment of shadow processes causing damage to the national budget. It might be valuable for fiscal state bodies, as well as for all law enforcement authorities, fighting against “shadow merchants.” The conclusion includes recommendations on statistical calculations of damage to the country’s budget and combating shadow economic processes. The final conclusion presents a need to improve the tax legislation and integrate these statistics agencies with the information of line ministries and institutions. The findings and recommendations have universal relevance for developed and developing countries. Keywords: the shadow economy, the informal economy, the criminal economy, the national accounts system. JEL Classifications: H26, Ðž17